1974
DOI: 10.1111/j.1471-4159.1974.tb04389.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carbohydrate Substrates, Amino Acids and Ammonia in the Brain During Insulin‐induced Hypoglycemia

Abstract: —The influence of insulin‐induced hypoglycemia upon carbohydrate substrates, amino acids and ammonia in the brain was studied in lightly anaesthetized rats, and the changes observed were related to the blood glucose concentration and to the EEG. Calculations from glucose concentrations in tissue, CSF and blood indicated the presence of appreciable amounts of free intracellular glucose at blood glucose concentrations above 3 μmol/g. When the blood glucose concentration fell below 3 μmol/g, there was no calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
2

Year Published

1976
1976
1997
1997

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(99 citation statements)
references
References 37 publications
7
90
2
Order By: Relevance
“…4 ' 17 -18 Similarly, when blood or plasma glucose decreases under the influence of insulin, brain glucose will also tend to decrease. 19 Data from the present study and from a recent study from our laboratory 9 supported these conclusions, but additionally demonstrated that for a given blood or plasma glucose concentration, diabetic rats had a greater concentration of glucose in the brain than did normoglycemic nondiabetic rats.…”
Section: Resultssupporting
confidence: 79%
“…4 ' 17 -18 Similarly, when blood or plasma glucose decreases under the influence of insulin, brain glucose will also tend to decrease. 19 Data from the present study and from a recent study from our laboratory 9 supported these conclusions, but additionally demonstrated that for a given blood or plasma glucose concentration, diabetic rats had a greater concentration of glucose in the brain than did normoglycemic nondiabetic rats.…”
Section: Resultssupporting
confidence: 79%
“…However, a number of investigations suggest that in very severe hypoglycemia, the amount of glutamate in the brain falls (Lewis et a!., 1974;Gore!! et a!., 1976;Enge!sen and Fonnum, 1983), although very little decrease is observed when blood glucose levels are varied in the range compatible with normal brain function (Engelsen and Fonnum, 1983).…”
mentioning
confidence: 99%
“…The concentration of creatine plus phosphosphocreatine in the brain was assumed to be 10.5 mM (14). From these observations, and assuming a linear relationship between concentration and SNR, and volume and SNR, we estimate that a proton species at a concentration of about 0.9 mM in a volume of 8 ml with 4 minutes of acquisition time at a field strength of 2.1 Tesla would yield a SNR of 5.…”
Section: Nmr Approach To Measurement Of the Pentose Phosphate Pathwaymentioning
confidence: 99%